Pendekatan Restoratif Sebagai Alternatif Pemidanaan Dalam Sistem Peradilan Pidana Indonesia - Yogie, Muhammad Yogie Adha; Akuntari, Nur Intan (Lex Stricta : Jurnal Ilmu Hukum, 2025)
This paper discusses the restorative justice approach as an alternative to punishment in the Indonesian criminal justice system. The massive use of imprisonment has caused serious problems such as the overcapacity of correctional institutions and the lack of recovery for victims. Restorative justice comes as a response to the weaknesses of the traditional punishment system that overemphasizes the punishment aspect, and is not effective in solving the problem of crime as a whole. The results showed that restorative justice offers a more comprehensive solution by prioritizing victim recovery, social reconciliation, and offender accountability without always relying on conventional punishment. The study results show that restorative justice has the potential to be a more humanist, adaptive, and effective punishment solution, especially in dealing with minor crimes. Several challenges such as the resistance of a rigid legal culture, the lack of understanding of the community and law enforcement officials, and the need for policy harmonization need to be considered. However, the implementation of this approach must be carried out while still paying attention to certain limitations and conditions so as not to cause imbalances in law enforcement.